African Soil Protection Law Mapping out options for a model legislation for improved sustainable soil management in Africa - a comparative legal analysis from Kenya, Cameroon and Zambia - Ginzky, Harald; C. Ruppe, Oliver (Recht und Verfassung in Afrika - Law and Constitution in Africa, 2021)
The protection of soil and the sustainable management of soils is a precondition for sustainable development, food security and the survival of humankind. Africa is the continent with the least land degradation. Yet, the pressure on soils is already enormous and continuously increasing due to a range of factors, including poverty, over-exploitation, population growth and climate change. Drivers of unsustainable soil management include overstocking, overgrazing, water erosion, landslides, and over-application of agro-chemicals. In light of this, the underlying legal, societal and political conditions have been comparatively analysed in "African Soil Protection Law". Distinct country studies from Kenya, Cameroon and Zambia serve to comparatively expose the serious impediments of soil in Africa. While mapping out options for model legislation for improved sustainable soil management in Africa, the publication addresses intertwined, interdisciplinary and complex questions pertaining to soils, which may also be of comparative interest to other continents and jurisdictions.